Clinical characterization of dystonia in adult patients with Huntington's disease. (29th June 2017) - van de Zande, N. A.; Massey, T. H.; McLauchlan, D.; Pryce Roberts, A.; Zutt, R.; Wardle, M.; Payne, G. C.; Clenaghan, C.; Tijssen, M. A. J.; Rosser, A. E.; Peall, K. J.
Abstract : Background and purpose: Huntington's disease (HD) is an autosomal dominant, neurodegenerative movement disorder, typically characterized by chorea. Dystonia is also recognized as part of the HD motor phenotype, although little work detailing its prevalence, distribution, severity and impact on functional capacity has been published to date. Methods: Patients (>18 years of age) were recruited from the Cardiff (UK) HD clinic, each undergoing a standardized videotaped clinical examination and series of functional assessment questionnaires (Unified Huntington's Disease Rating Scale, Burke–Fahn–Marsden Dystonia Rating Scale and modified version of the Toronto Western Spasmodic Torticollis Rating Scale). The presence and severity of dystonia were scored by four independent neurologists using the Burke–Fahn–Marsden Dystonia Rating Scale and Unified Huntington's Disease Rating Scale. Statistical analysis included Fisher's exact test, Wilcoxon test, anova and calculation of correlation coefficients where appropriate. Results: Forty‐eight patients [91% (48/53)] demonstrated evidence of dystonia, with the highest prevalence in the left upper limb ( n = 44, 83%), right upper limb most severely affected and eyes least affected. Statistically significant positive correlations ( P < 0.05) were observed between dystonia severity and increasing HD disease stage and motor disease duration. Deterioration in functional capacity also correlated with increasing dystonia severity. No significant relationship was observed with age at motor symptom onset or CAG repeat length. Conclusions: We report a high prevalence of dystonia in adult patients with HD, with worsening dystonia severity with increasing HD disease stage and motor disease duration. The recognition and management of dystonic symptoms in routine clinical practice will aid overall symptomatic treatment and functional improvement.